2020
DOI: 10.5812/ijcm.100717
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tachykinins in the Initiation and Progression of Gastrointestinal Cancers: A Review

Abstract: Context: Tachykinins (TKs), an evolutionarily conserved family of peptide hormones, are widely distributed within the peripheral and central nervous systems. TKs exert their biological actions in many processes via three subtypes of transmembrane G-protein coupled receptors, which are NK1R, NK2R, and NK3R. Although the mechanisms that connect TKs peptide activity to physiological processes are currently precise, it has been shown that TKs over-activation is associated with the pathogenesis of many diseases, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Several studies have recently demonstrated that SP induces a series of signaling pathways through NK1R that mediate cellular excitability in several human tumor cells. It has important roles in forming and spreading various tumor cells via migration, angiogenesis, and metastasis [11][12][13][14][15][16]. is is important since the prevention of metastasis is a major goal in treating tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently demonstrated that SP induces a series of signaling pathways through NK1R that mediate cellular excitability in several human tumor cells. It has important roles in forming and spreading various tumor cells via migration, angiogenesis, and metastasis [11][12][13][14][15][16]. is is important since the prevention of metastasis is a major goal in treating tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mammals and other vertebrates showed that tachykinin shared conservative carboxyl-terminal sequence, -FXGLM-NH 2 (38,39). The four NKBs of Japanese eel generated from two tac3 genes presented the common C-terminal motif (-FVGLM-NH 2 ), which is also found in zebrafish (22), goldfish (23), and spotted sea bass (29).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC), gastric cancer (GC), gallbladder cancer, hepatocellular carcinoma (HCC), esophageal cancer, pancreatic cancer, and anal cancer are some of the most well-known malignancies that threaten the life of a considerable number of people globally [2,3]. Nowadays, we know that genetics and epigenetics aberrancies could convert normal gastrointestinal cells into neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%